Clinical-Psychopathological Aspects of Remote Period in Closed Traumatic Brain Injury - Kazakov, V. Ye. (Psychiatry, Neurology and Medical Psychology, 2015)
We studied 437 people who have suff ered from traumatic brain injury, which had a psychopathology consequences. The received results revealed that remote period of TBI presents a variety of clinical psychopathology forms. At the same time there is some phasing fl ow of TBI consequences. Already in the early stages predictors of adverse current, which leads to disruption of the functioning of the patient can be identifi ed.